A Ratiometric Two‐Photon Fluorescent Probe for Tracking Lysosomal ATP: Direct In Cellulo Observation of Lysosomal Membrane Fusion Processes. (18th July 2018) - Jun, Yong Woong; Wang, Taejun; Hwang, Sekyu; Kim, Dokyoung; Ma, Donghee; Kim, Ki Hean; Kim, Sungjee; Jung, Junyang; Ahn, Kyo Han
Abstract: Vesicles exchange their contents through membrane fusion processes, kiss‐and‐run and full‐collapse fusion. Indirect observation of these fusion processes using artificial vesicles enhanced our understanding on the molecular mechanisms involved. Direct observation of the fusion processes in a real biological system, however, remains a challenge owing to many technical obstacles. We report a ratiometric two‐photon probe offering real‐time tracking of lysosomal ATP with quantitative information for the first time. By applying the probe to two‐photon live‐cell imaging, the lysosomal membrane fusion process in cells has been directly observed and the concentration of its content, lysosomal ATP, has been measured. Results show that the kiss‐and‐run process between lysosomes proceeds through repeated transient interactions with gradual content mixing, whereas the full‐fusion process occurs at once. Furthermore, it is confirmed that both the fusion processes proceed with conservation of the content. Such a small‐molecule probe exerts minimal disturbance and hence has potential for studying various biological processes associated with lysosomal ATP.